NH2-ZnS-coated beta-CD-MOF fluorescent composite material as well as preparation method and application thereof

Through NH2-ZnS@β-CD-MOF fluorescent composite material, the problem of insufficient MOF toxicity and detection sensitivity in fluorescent sensors is solved, and a fluorescent sensor with low toxicity and high detection limit is realized, which can effectively detect formaldehyde and 4-chlorine. phenol.

CN119286508AActive Publication Date: 2025-01-10XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411207214.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The metal organic frame (MOF) materials used in existing fluorescence sensors are toxic and have insufficient detection limits for formaldehyde and 4-chlorophenol.

Method used

Using NH2-ZnS@β-CD-MOF fluorescent composite material, the composite material is formed by stirring β-cyclodextrin and functionalized zinc sulfide (ZnS) under dark conditions. It is used to prepare fluorescent sensors, reducing the toxicity of MOF and improving the detection sensitivity.

Benefits of technology

A fluorescent composite material with low toxicity, excellent luminescence performance and high yield is achieved, which can effectively detect formaldehyde and 4-chlorophenol in aqueous solution, and the detection limit is improved to 1.6 nmol/L and 3.3 nmol/L.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286508A_ABST
    Figure CN119286508A_ABST
Patent Text Reader

Abstract

The invention provides an NH2-ZnS-coated beta-CD-MOF fluorescent composite material, a preparation method and application, specifically, beta-CD-MOF and NH2-ZnS are dissolved in a methanol solution, stirring is performed under a dark condition, centrifugation is performed to obtain a white precipitate, the obtained white precipitate is washed with the methanol solution, and the washed white precipitate is subjected to vacuum drying under the dark condition to obtain the beta-CD-MOF fluorescent composite material. And preparing the NH2-ZnS (at) beta-CD-MOF fluorescent composite material. The fluorescent composite material is used for preparing a fluorescent sensor. The fluorescence sensor disclosed by the invention not only can realize low-concentration linear detection of formaldehyde, but also can be used for detecting 4-chlorophenol in an aqueous solution, and when the concentration of NH2-ZnS-beta-CD-MOF is 0.7 mg / mL, the composite material is dispersed in deionized water, the luminous intensity is the maximum, and a good linear relationship can be shown between formaldehyde and 4-chlorophenol in a certain concentration range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic pollutant detection, relates to a fluorescent sensor, and relates to an NH2-ZnS@β-CD-MOF fluorescent composite material, a preparation method and an application thereof. Background Art

[0002] Fluorescence sensors are widely used to detect harmful substances such as formaldehyde and 4-chlorophenol due to their high selectivity, simple operation, low cost, real-time detection and short response time. Among these fluorescence sensors, sensors based on metal organic frameworks (MOFs) are more attractive in terms of structural characteristics, functional composition and interaction between MOFs and analytes. However, due to the presence of metals such as Cd, Cu and Zn in MOFs, they will cause certain harm to the environment. Summary of the invention

[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide an NH2-ZnS@β-CD-MOF fluorescent composite material, a preparation method and an application thereof, so as to solve the technical problem that the toxicity of MOF used in the fluorescent sensor in the prior art needs to be further reduced.

[0004] Another object of the present invention is to provide an NH2-ZnS@β-CD-MOF fluorescent composite material, a preparation method and an application thereof, so as to solve the technical problem that the detection limit of the fluorescent sensor for formaldehyde and 4-chlorophenol in the prior art needs to be further improved.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0006] A method for preparing an NH2-ZnS@β-CD-MOF fluorescent composite material, the method comprising the following steps:

[0007] Step 1, preparation of β-CD-MOF:

[0008] β-CD (i.e., β-cyclodextrin) and KOH were dissolved in deionized water, sonicated and filtered, methanol solution was added to the filtrate, and the mixture was sealed and placed at room temperature to produce white crystals after methanol vapor diffusion. The white crystals were washed and filtered, and vacuum dried to obtain β-CD-MOF.

[0009] Step 2, preparation of NH2-ZnS:

[0010] Dissolve Zn(NO3)2·6H2O and CH4N2S in a mixture of ethylenediamine and deionized water, stir and transfer to a hydrothermal reactor, keep warm for reaction, cool to room temperature after the reaction is completed, obtain a white precipitate, centrifuge and wash until the supernatant is colorless and transparent, and vacuum dry to obtain NH2-ZnS.

[0011] Step 3: Preparation of NH2-ZnS@β-CD-MOF fluorescent composite material:

[0012] The β-CD-MOF obtained in step one and the NH2-ZnS obtained in step two were dissolved in a methanol solution, stirred under dark conditions and then centrifuged to obtain a white precipitate, and the obtained white precipitate was washed with a methanol solution. The washed white precipitate was vacuum dried under dark conditions to obtain an NH2-ZnS@β-CD-MOF fluorescent composite material.

[0013] The present invention also has the following technical features:

[0014] In step 1, 2.84 g of β-CD and 1.12 g of KOH were added to every 100 mL of deionized water.

[0015] In step 2, 0.297 g of Zn(NO3)2·6H2O and 0.228 g of CH4N2S were dissolved in 50 mL of ethylenediamine and stirred for 0.5 h, and then 10 mL of deionized water was added and stirring was continued for 0.5 h.

[0016] In step 2, the temperature of the hydrothermal reactor is 110°C.

[0017] In step three, the mass ratio of β-CD-MOF obtained in step one and NH2-ZnS obtained in step two is (1-5):1.

[0018] Preferably, in step three, the mass ratio of β-CD-MOF obtained in step one to NH2-ZnS obtained in step two is 4:1.

[0019] In step 3, the β-CD-MOF obtained in step 1 and the NH2-ZnS obtained in step 2 were dissolved in 20 mL of methanol solution.

[0020] In step 3, the mixture was stirred in the dark for 6 h.

[0021] The present invention also protects an NH2-ZnS@β-CD-MOF fluorescent composite material, which is prepared by the preparation method of the NH2-ZnS@β-CD-MOF fluorescent composite material as described above.

[0022] The present invention also protects the use of the NH2-ZnS@β-CD-MOF fluorescent composite material described above for preparing a fluorescent sensor.

[0023] The fluorescent sensor is used to detect formaldehyde and 4-chlorophenol.

[0024] The dispersion concentration of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is 0.5 mg / mL to 0.9 mg / mL.

[0025] Preferably, the dispersion concentration of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is 0.7 mg / mL.

[0026] The dispersion solvent of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is N'N-dimethylformamide, methanol, acetone, anhydrous ethanol, acetonitrile or deionized water.

[0027] Compared with the prior art, the present invention has the following technical effects:

[0028] (I) The fluorescent composite material of the present invention has excellent luminescent properties. The MOF used is β-cyclodextrin (i.e., β-CD). The raw material is green, safe, cheap and easy to obtain. It can not only improve the toxic defects of traditional MOF materials, but also effectively reduce the harm of MOF organic matter to the environment.

[0029] (II) The fluorescent composite material of the present invention is β-cyclodextrin-MOF composite amino-functionalized quantum dots NH2-ZnS@β-CD-MOF, which has high yield, unique photoluminescence properties and low toxicity, and provides a new idea for the development of fluorescent sensors.

[0030] (III) The fluorescent sensor constructed with the NH2-ZnS@β-CD-MOF fluorescent composite material of the present invention can not only realize low-concentration linear detection of formaldehyde, but also can be used for the detection of 4-chlorophenol in aqueous solution. When the concentration of NH2-ZnS@β-CD-MOF is 0.7 mg / mL, the luminescence intensity of the composite material dispersed in deionized water is the largest, and a good linear relationship can be shown for both formaldehyde and 4-chlorophenol within a certain concentration range.

[0031] (IV) The detection limit of the fluorescent sensor constructed with the NH2-ZnS@β-CD-MOF fluorescent composite material of the present invention for formaldehyde is 1.6 nmol / L; the detection limit for 4-chlorophenol is 3.3 nmol / L. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1(a) is the FTIR spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0033] Figure 1(b) is the full XPS spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0034] Figure 1(c) is the XPS Zn2p spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0035] Figure 1(d) is the XPS S2p spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0036] Figure 1(e) is the XPS O1s spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0037] Figure 1(f) is the XPS C1s spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0038] Figure 2 Fluorescence emission intensity spectra of NH2-ZnS, β-CD-MOF and NH2-ZnS@β-CD-MOF at 330 nm.

[0039] Figure 3 The fluorescence spectra of formaldehyde by the fluorescence sensor with mass ratios of NH2-ZnS and β-CD-MOF being 1:2, 1:3, 1:4 and 1:5 respectively.

[0040] Figure 4 The fluorescence spectra of 4-chlorophenol of the fluorescence sensor with mass ratios of NH2-ZnS and β-CD-MOF being 1:2, 1:3, 1:4 and 1:5 respectively.

[0041] Figure 5 The fluorescence spectra of NH2-ZnS@β-CD-MOF fluorescent composite materials with different dispersion concentrations.

[0042] Figure 6 Fluorescence spectrum of the dispersed solvent of the fluorescent sensor constructed for the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0043] Figure 7 Fluorescence spectra of the fluorescence sensor constructed with NH2-ZnS@β-CD-MOF fluorescent composite material for detecting formaldehyde (a, b) and 4-chlorophenol (c, d), as well as the linear relationship between fluorescence intensity and formaldehyde concentration.

[0044] The specific contents of the present invention are further explained in detail below in conjunction with embodiments. DETAILED DESCRIPTION

[0045] It should be noted that, unless otherwise specified, all raw materials and instruments used in the present invention are those known in the prior art. For example, β-cyclodextrin (ie, β-CD) is commercially available β-cyclodextrin.

[0046] The specifications of the instruments and raw materials used in the present invention are as follows:

[0047] Electronic analytical balance, Shenyang Longteng Electronic Weighing Instrument Co., Ltd.

[0048] Electric heating blast drying oven, Beijing Kewei Yongxing Instrument Co., Ltd.

[0049] Ultrasonic cleaning machine, Zhejiang Ningbo Instrument Co., Ltd.

[0050] Magnetic heating stirrer, Changzhou Guohua Electric Co., Ltd.

[0051] Scanning electron microscope, Carl Zeiss GmbH.

[0052] Vacuum drying oven, Tianjin Test Instrument Co., Ltd.

[0053] β-Cyclodextrin, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0054] Thiourea, Sinopharm Chemical Reagent Co., Ltd.

[0055] Zinc nitrate hexahydrate, Shanghai Jingchun Biochemical Technology Co., Ltd.

[0056] Potassium hydroxide, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0057] Ethylenediamine, Sinopharm Chemical Reagent Co., Ltd.

[0058] Methanol, Sinopharm Chemical Reagent Co., Ltd.

[0059] Formaldehyde, Xilong Chemical Co., Ltd.

[0060] 4-Chlorophenol, Sinopharm Chemical Reagent Co., Ltd.

[0061] In the present invention, the metal organic framework (β-CD-MOF) of cyclodextrin may be an effective way to replace common MOFs. However, the optical signal of β-CD-MOF itself is poor, and its direct use for fluorescence measurement is limited. The present invention introduces luminescent quantum dots (QDs) into β-CD-MOF to solve this defect. Zinc sulfide (ZnS) has a large exciton binding energy. The present invention further functionalizes and modifies ZnS, and then uses the modified ZnS (i.e., NH2-ZnS) as luminescent quantum dots (QDs), that is, the NH2-ZnS@β-CD-MOF fluorescent composite material in the present invention is prepared by NH2-ZnS and β-CD-MOF. The fluorescent sensor prepared using the NH2-ZnS@β-CD-MOF fluorescent composite material of the present invention can improve the specific detection and detection limit of pollutants by existing fluorescent sensors.

[0062] It should be noted that, in the present invention, the formaldehyde solution is prepared by measuring 0.24 mL of 37 wt.% formaldehyde solution and diluting it in a 50 mL volumetric flask, and then taking 5 mL of the solution and diluting it in a 50 mL volumetric flask to prepare a concentration gradient of 50 mmol / L, 5 mmol / L, 500 μmol / L, 50 μmol / L, 5 μmol / L, and 0.5 μmol / L of the formaldehyde test solution.

[0063] In the present invention, the 4-chlorophenol solution is prepared by measuring 5 mL of 0.05 mol / L 4-chlorophenol solution and diluting it into a 50 mL volumetric flask, and then taking 5 mL of the solution and diluting it into a 50 mL volumetric flask to prepare a 4-chlorophenol test solution with a concentration gradient of 1 mmol / L, 0.1 mmol / L, 10 μmol / L, and 1 μmol / L.

[0064] The room temperature in the present invention refers to the natural environment temperature during the production process. Usually, the temperature is generally within the range of 20±10°C.

[0065] In the present invention, the excitation wavelength during fluorescence testing is 300 nm, the slit width is 5 nm, and the gain is 1.

[0066] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.

[0067] Embodiment 1:

[0068] This embodiment provides a method for preparing a NH2-ZnS@β-CD-MOF fluorescent composite material, which comprises the following steps:

[0069] Step 1, preparation of β-CD-MOF:

[0070] Dissolve 2.84g β-CD and 1.12g KOH in 100mL deionized water, disperse by ultrasound for 30min, filter the solution through a 0.45μm filter, transfer the solution to a 250mL beaker, add 100mL methanol solution, seal the beaker, and place it at room temperature for 5-7 days. Collect the white crystals and spin at a speed of 3000r / min. -1 The mixture was centrifuged for 5 min, washed with anhydrous ethanol three times, and vacuum dried at 45 °C for 12 h to obtain β-CD-MOF.

[0071] Step 2, preparation of NH2-ZnS:

[0072] Dissolve 0.297g Zn(NO3)2·6H2O and 0.228g CH4N2S in 50mL ethylenediamine, stir for 0.5h, add 10mL deionized water to the solution, and continue stirring for 0.5h. Transfer the mixture to a polytetrafluoroethylene reactor and react at 110℃ for 24h. After the reaction is completed, cool the reactor to room temperature and heat at a speed of 3000r·min. -1 , centrifuged for 5 minutes, and the obtained white precipitate was washed three times with anhydrous ethanol until the supernatant was colorless and transparent, and then dried under vacuum conditions at 60°C for 12 hours to obtain NH2-ZnS.

[0073] Step 3: Preparation of NH2-ZnS@β-CD-MOF fluorescent composite material:

[0074] Weigh 25 mg NH2-ZnS and 100 mg β-CD-MOF, dissolve the two raw materials in 20 mL methanol solution, and stir for 6 h in the dark at a speed of 3000 r·min. -1 , centrifuged for 5 min, the supernatant was discarded, and 5 mL of methanol solution was added to wash the white precipitate three times. The white precipitate after centrifugation was vacuum dried at 60 ° C for 12 h in the dark to obtain NH2-ZnS@β-CD-MOF fluorescent composite material.

[0075] Figure 1(a) shows the infrared spectra of β-CD-MOF, NH2-ZnS and NH2-ZnS@β-CD-MOF fluorescent composites. NH2-ZnS@β-CD-MOF and β-CD-MOF have a wavelength of 3500-3000 cm -1 The positions of the characteristic absorption peaks are similar to those at , and the peaks of -OH, CH, and C=O are at 3300-3500, 2930, and 1654 cm-1, respectively. -1 The symmetrical deformation vibration peak of the CO skeleton appears at 1030 cm -1 In the infrared spectrum of NH2-ZnS, 3242cm -1 and 1578cm -1 The absorption peak at 2939 cm is attributed to the NH vibration of the primary amine. -1 The peaks at 639 cm -1 The peak at is the typical Zn-S vibration peak of ZnS. These results confirm the successful synthesis of NH2-ZnS. By comparing the infrared spectra of NH2-ZnS@β-CD-MOF and β-CD-MOF, the Fourier transform infrared peak of NH2-ZnS@β-CD-MOF is at 1651cm -1 and 2930cm -1The peak intensity at 1026 cm-1 is increased, which is related to the NH bending vibration of NH2-ZnS. -1 and 1654cm -1 The wavelength shifts to the short-wave direction, which is the interaction of hydrogen bonds between NH2-ZnS and β-CD-MOF composite materials. The above results show that the NH2-ZnS@β-CD-MOF fluorescent composite material was successfully synthesized.

[0076] Figure 1(b) is the full XPS spectrum of the NH2-ZnS@β-CD-MOF fluorescent composite material; it can be seen from Figure 1(b) that NH2-ZnS@β-CD-MOF contains Zn, S, O and C elements.

[0077] From Figure 1(c), it can be concluded that the two peaks of the Zn2p spectrum of NH2-ZnS@β-CDs-MOF at 1020.0 and 1044.2 eV correspond to the Zn2p of ZnS, respectively. 3 / 2 and Zn2p 1 / 2 The spin-orbit peak and the characteristic peak difference are 24.2 eV, which indicates that Zn in ZnS is mainly in the form of Zn 2+ exist.

[0078] In Figure 1(d), the XPS spectrum of S2p shows two characteristic peaks near 161.8 eV. These two peaks are located at 161.8 eV and 159.7 eV, corresponding to S2p 1 / 2 and S2p 3 / 2 , and the characteristic peak difference is 2.1eV, so S in ZnS is mainly S 2- form.

[0079] The O1s spectrum in Figure 1(e) shows peaks at binding energies of 532.4, 531.5, and 530.7 eV, which correspond to C=O, CO, and surface-adsorbed -OH, respectively.

[0080] The XPS spectrum of C1s in Figure 1(f) has binding energy peaks at 286.0 and 284.6 eV, corresponding to CO and C=O, respectively. These results also indicate that the NH2-ZnS@β-CD-MOF fluorescent composite material was successfully synthesized.

[0081] Figure 2 The interaction between NH2-ZnS and β-CD-MOF was studied by analyzing the fluorescence spectra of NH2-ZnS, β-CD-MOF and NH2-ZnS@β-CD-MOF. Figure 2As shown in the figure, when the excitation wavelength is 300nm, all three materials have a strong emission peak at a wavelength of 330nm. Compared with β-CD-MOF and NH2-ZnS@β-CD-MOF, the fluorescence intensity of NH2-ZnS is higher, which is due to the large amount of NH2 modification on the surface of ZnS. These defects can produce variable energy gaps and enhance the fluorescence intensity of ZnS. β-CD-MOF has the lowest fluorescence intensity, which is because a large amount of β-CD-MOF will aggregate in the solution, resulting in low fluorescence intensity. After adding NH2-ZnS, the fluorescence intensity increases, which is because the hydrophobic hydroxyl group of β-CD-MOF will form hydrogen bonds with the amino group of NH2-ZnS. The formation of hydrogen bonds will increase the stability of β-CD-MOF, thereby reducing the energy loss of β-CD-MOF due to spin transition in a non-radiative form. The above results also show that the fluorescence intensity of the NH2-ZnS@β-CD-MOF fluorescent composite material comes from NH2-ZnS quantum dots, so the NH2-ZnS@β-CD-MOF fluorescent composite material can be used to construct a fluorescent sensor.

[0082] Embodiments 2 to 4:

[0083] This embodiment provides a method for preparing a NH2-ZnS@β-CD-MOF fluorescent composite material. The method is basically the same as the preparation method in Example 1, with the only difference being that in step three, the ratio of NH2-ZnS to β-CD-MOF is different. In this embodiment, the mass ratios of NH2-ZnS to β-CD-MOF are 1:2, 1:3 and 1:5, respectively.

[0084] Example 5: (different mass ratios)

[0085] This example provides an application of the NH2-ZnS@β-CD-MOF fluorescent composite material for preparing a fluorescent sensor. The fluorescent sensor is used to detect formaldehyde and 4-chlorophenol.

[0086] This example tests the effect of different mass ratios of NH2-ZnS and β-CD-MOF (NH2-ZnS to β-CD-MOF mass ratios of 1:2, 1:3, 1:4 and 1:5, respectively) on the fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material. This example gives the application conditions of the fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material and the linear concentration range and detection limit for formaldehyde and 4-chlorophenol.

[0087] In this embodiment, the preparation process of the fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material is as follows: weigh 7 mg of NH2-ZnS@β-CD-MOF fluorescent composite material powder and dissolve it in 10 mL of deionized water, ultrasonically disperse it for 30 minutes to form a uniformly dispersed suspension, and measure 2 mL of the above dispersion into a cuvette to obtain a fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material.

[0088] The analysis of formaldehyde by the fluorescent sensor constructed with NH2-ZnS@β-CD-MOF fluorescent composite material mainly depends on the influence of the luminescence intensity of the NH2-ZnS@β-CD-MOF fluorescent composite material, and the change of its fluorescence intensity is mainly related to the synthesis ratio of NH2-ZnS and β-CD-MOF complex.

[0089] like Figure 3 As shown in the figure, four groups of experiments were designed, namely 1:2, 1:3, 1:4 and 1:5 for formaldehyde detection. As can be seen from the figure, when the ratio of NH2-ZnS to β-CD-MOF increases from 1:2 to 1:5, the fluorescence intensity of NH2-ZnS@β-CD-MOF also increases first and then decreases with the increase of β-CD-MOF mass. When the mass ratio is 1:4, the fluorescence intensity reaches the maximum. The above results show that when the mass ratio of NH2-ZnS to β-CD-MOF is 1:4, it is the optimal ratio for the fluorescent sensor constructed by NH2-ZnS@β-CD-MOF fluorescent composite material to detect formaldehyde.

[0090] Figure 4 The fluorescence intensity spectrum of 4-chlorophenol constructed from NH2-ZnS@β-CD-MOF fluorescent composite materials with different mass ratios of NH2-ZnS and β-CD-MOF as a fluorescent sensor. Figure 4 It can be seen that when the ratio of NH2-ZnS to β-CD-MOF increases from 1:2 to 1:5, the fluorescence intensity of NH2-ZnS@β-CD-MOF also increases first and then decreases with the increase of β-CD-MOF mass. When the molar ratio is 1:4, the fluorescence intensity reaches the maximum, because NH2-ZnS is the main luminescent source of the composite material. When the mass of NH2-ZnS is too large, the fluorescence intensity decreases, which may be because a large amount of NH2-ZnS agglomerates, causing part of the energy to transition as non-radiative energy, thereby reducing the fluorescence intensity. From the fluorescence spectrum, it can be seen that the mass ratio of NH2-ZnS to β-CD-MOF is 1:4, which is the optimal ratio for the fluorescent sensor constructed by NH2-ZnS@β-CD-MOF fluorescent composite material to detect 4-chlorophenol.

[0091] Example 6: (Different dispersion concentrations)

[0092] This example shows the application of the NH2-ZnS@β-CD-MOF fluorescent composite material (i.e., the mass ratio of NH2-ZnS to β-CD-MOF is 1:4) in Example 1 for preparing a fluorescent sensor. The fluorescent sensor is used to detect formaldehyde and 4-chlorophenol.

[0093] In this embodiment, the preparation process of the fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material is basically the same as that in Example 5, the only difference is that in this embodiment, 5 mg, 6 mg, 7 mg, 8 mg and 9 mg of NH2-ZnS@β-CD-MOF fluorescent composite material powder are weighed in sequence and dissolved in 10 mL of deionized water.

[0094] In order to achieve the best fluorescence detection performance of the fluorescent sensor constructed by NH2-ZnS@β-CD-MOF fluorescent composite material for formaldehyde and 4-chlorophenol, the fluorescence experimental conditions of NH2-ZnS@β-CD-MOF fluorescent composite material should be optimized. In 10mL of deionized water, different masses of NH2-ZnS@β-CD-MOF fluorescent composite material (5mg, 6mg, 7mg, 8mg and 9mg) were weighed and ultrasonically dispersed for 20min. Figure 5 As shown in the figure, with the increase of NH2-ZnS@β-CD-MOF dispersion concentration, the fluorescence intensity also increases, and when the concentration of NH2-ZnS@β-CD-MOF dispersion is 0.7mg / mL, the fluorescence intensity of the fluorescence sensor reaches the maximum. Continuing to increase the concentration of NH2-ZnS@β-CD-MOF, the fluorescence intensity decreases. This may be because a large number of fluorescent substances agglomerate, causing the fluorescence to transition in a non-radiative form, consuming part of the energy and reducing the fluorescence intensity. The above results show that the concentration of NH2-ZnS@β-CD-MOF is 0.7mg / mL, which is the optimal concentration of the fluorescence sensor.

[0095] Example 7: (Different dispersion solvents)

[0096] This example shows the use of the NH2-ZnS@β-CD-MOF fluorescent composite material in Example 1 (i.e., the mass ratio of NH2-ZnS and β-CD-MOF is 1:4) for preparing a fluorescent sensor.

[0097] In this embodiment, the preparation process of the fluorescent sensor constructed with the NH2-ZnS@β-CD-MOF fluorescent composite material is basically the same as that in Example 5, with the only difference being that in this embodiment, the dispersion solvents examined are N'N-dimethylformamide, methanol, acetone, anhydrous ethanol, acetonitrile or deionized water.

[0098] Since the dispersed solvent system has a great influence on the detection of the fluorescence sensor, several commonly used solutions were selected as the research objects. In this example, the influence of the dispersed solvent of the fluorescence sensor on the fluorescence intensity of NH2-ZnS@β-CD-MOF was studied at an excitation wavelength of 300nm. Figure 6 It can be seen that when the NH2-ZnS@β-CD-MOF fluorescent composite material is dispersed in different dispersion solvents, the fluorescence intensity of the sensor is different, which is related to the polarity of the dispersion solvent. As can be seen from the figure, the fluorescence intensity of the NH2-ZnS@β-CD-MOF fluorescent composite material dispersed in deionized water is the highest, and the fluorescence intensity of the NH2-ZnS@β-CD-MOF fluorescent composite material dispersed in acetone dispersion solvent is the lowest. This is because the polarity of deionized water is much greater than that of acetonitrile, DMF and methanol, and its fluorescence intensity also changes with the change of dispersion solvent. This proves that the fluorescence intensity is consistent with the polarity of the dispersion solvent. The above results show that the polarity of the dispersion solvent will affect the fluorescence intensity of the fluorescence sensor, and the polarity is positively correlated with the fluorescence intensity.

[0099] Example 8: (Investigation of detection limit)

[0100] This example shows the application of the NH2-ZnS@β-CD-MOF fluorescent composite material (i.e., the mass ratio of NH2-ZnS to β-CD-MOF is 1:4) in Example 1 for preparing a fluorescent sensor. The fluorescent sensor is used to detect formaldehyde and 4-chlorophenol.

[0101] In this embodiment, the preparation process of the fluorescent sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material is the same as that in Example 5.

[0102] The fluorescence spectra of the fluorescence sensor constructed by the NH2-ZnS@β-CD-MOF fluorescent composite material prepared in this example for detecting formaldehyde and 4-chlorophenol, as well as the linear relationship between fluorescence intensity and formaldehyde concentration are shown in Figure 2. Figure 7 shown.

[0103] Figure 7 (a) is the fluorescence intensity of the fluorescence sensor constructed by NH2-ZnS@β-CD-MOF fluorescent composite material at 330nm as the formaldehyde concentration changes. As the formaldehyde concentration increases, the fluorescence intensity gradually increases. In addition, Figure 7 (b) shows that the formaldehyde concentration is 5.0×10 -3 In the range of μmol / L to 1.0 μmol / L, the fluorescence signal changes with the increase of concentration. The linear equation can be expressed as: F = 2087lgC (μmol / L) + 6327, (R 2=0.995), from which it was calculated that the detection limit of formaldehyde for the fluorescence sensor constructed with NH2-ZnS@β-CD-MOF fluorescent composite material was 1.6nmol / L.

[0104] Figure 7 (c) shows the quantitative analysis of 4-chlorophenol by the fluorescent sensor constructed with NH2-ZnS@β-CD-MOF fluorescent composite material. It can be seen from the figure that when the concentration of 4-chlorophenol is 1.0×10 -2 In the range of μmol / L to 10μmol / L, the fluorescence intensity increases with the increase of 4-chlorophenol concentration; Figure 7 From (d) in the figure, we can see that the linear equation for the change of fluorescence intensity with 4-chlorophenol concentration is: F = 1175lgC (μmol / L) + 3896 (R 2 =0.994), from which it was calculated that the detection limit of the fluorescence sensor constructed with NH2-ZnS@β-CD-MOF fluorescent composite material for 4-chlorophenol was 3.3nmol / L.

[0105] The above results show that the fluorescent sensor constructed by NH2-ZnS@β-CD-MOF fluorescent composite material is expected to detect the above two pollutants. This is because β-CD-MOF has a unique three-dimensional ring structure and a fixed inner cavity size, which allows small molecules of FA and 4-CP to enter the cavity and react with NH2-ZnS with electron-rich functional groups to achieve sensitive detection of formaldehyde and 4-chlorophenol.

Claims

1. A method for preparing NH2-ZnS@β-CD-MOF fluorescent composite material, characterized in that: The method comprises the following steps: Step 1, preparation of β-CD-MOF: β-CD and KOH were dissolved in deionized water, ultrasonicated and filtered, methanol solution was added to the filtrate, sealed and placed at room temperature, white crystals were generated after methanol vapor diffusion, the white crystals were washed and filtered, and vacuum dried to obtain β-CD-MOF; Step 2, preparation of NH2-ZnS: Dissolve Zn(NO3)2·6H2O and CH4N2S in a mixture of ethylenediamine and deionized water, stir and transfer to a hydrothermal reactor, keep warm for reaction, cool to room temperature after the reaction is completed, obtain a white precipitate, centrifuge and wash until the supernatant is colorless and transparent, and vacuum dry to obtain NH2-ZnS; Step 3: Preparation of NH2-ZnS@β-CD-MOF fluorescent composite material: The β-CD-MOF obtained in step one and the NH2-ZnS obtained in step two were dissolved in a methanol solution, stirred under dark conditions and then centrifuged to obtain a white precipitate, and the obtained white precipitate was washed with a methanol solution. The washed white precipitate was vacuum dried under dark conditions to obtain an NH2-ZnS@β-CD-MOF fluorescent composite material.

2. The method for preparing the NH2-ZnS@β-CD-MOF fluorescent composite material according to claim 1, characterized in that: In step 1, 2.84 g of β-CD and 1.12 g of KOH were added to every 100 mL of deionized water.

3. The method for preparing the NH2-ZnS@β-CD-MOF fluorescent composite material according to claim 1, characterized in that: In step 2, 0.297 g of Zn(N03)2·6H20 and 0.228 g of CH4N2S were dissolved in 50 mL of ethylenediamine and stirred for 0.5 h, then 10 mL of deionized water was added and stirring was continued for 0.5 h; In step 2, the temperature of the hydrothermal reactor is 110°C.

4. The method for preparing the NH2-ZnS@β-CD-MOF fluorescent composite material according to claim 1, characterized in that: In step 3, the mass ratio of β-CD-MOF obtained in step 1 to NH2-ZnS obtained in step 2 is (1-5):1; In step 3, the β-CD-MOF obtained in step 1 and the NH2-ZnS obtained in step 2 were dissolved in 20 mL of methanol solution; In step 3, the mixture was stirred in the dark for 6 h.

5. A NH2-ZnS@β-CD-MOF fluorescent composite material, characterized in that: The fluorescent composite material is prepared by the preparation method of the NH2-ZnS@β-CD-MOF fluorescent composite material as claimed in any one of claims 1 to 4.

6. Use of the NH2-ZnS@β-CD-MOF fluorescent composite material as claimed in claim 5 for preparing a fluorescent sensor.

7. The use according to claim 6, characterized in that The fluorescent sensor is used to detect formaldehyde and 4-chlorophenol.

8. The use according to claim 6, characterized in that The dispersion concentration of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is 0.5 mg / mL to 0.9 mg / mL.

9. The use according to claim 8, characterized in that The dispersion concentration of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is 0.7 mg / mL.

10. The use according to claim 6, characterized in that The dispersion solvent of the NH2-ZnS@β-CD-MOF fluorescent composite material in the fluorescent sensor is N'N-dimethylformamide, methanol, acetone, anhydrous ethanol, acetonitrile or deionized water.

Citation Information

Patent Citations

  • Cyclodextrin metal frame circular polarization luminescent crystal, preparation method and applications thereof

    CN110845740A

  • Preparation method of cyclodextrin metal organic framework stably existing in water phase

    CN114656645A

  • Metal-organic framework and method for producing the same

    JP2023161337A